Zero Waste: Mewujudkan Masa Depan Ramah Lingkungan bagi Masyarakat Desa Jongkong - Weran, Yohana Triana Ina; Rais, Burhanudin; Mikha, Mikha (STAI Auliaurrasyidin Tembilahan, 2024)
Waste is a significant issue in society, both in Indonesia and globally. The primary challenges are the availability of landfills and the awareness of residents. Jongkong Pasar Village in Kapuas Hulu Regency, West Kalimantan Province, faces similar issues. Consequently, a Zero Waste-themed community service program was implemented to enhance residents' awareness in managing household waste, particularly plastic. This activity took place in January 2024 utilizing the counseling method. As a result, residents' understanding of waste management improved through the implementation of zero waste practices. This fosters great hope that those who were not present will emulate the actions of the participants. Consequently, the waste problem in Jongkong Pasar Village can be addressed promptly.